Modulation of spasticity in patients following a cerebrovascular accident in the subacute pase - Musuruana, Agustín; Ricardo Revelant, Martin (International Journal of Neurology, 2024)
Spasticity is a common complication in patients diagnosed with stroke. Various therapeutic approaches have been developed to address this problem. However, it is important to review the latest updates on these approaches through rigorous clinical trials to determine which approaches are most widely used and effective. The overall objective of this research is to describe the therapeutic approaches applied in clinical trials aimed at modulating spasticity in patients diagnosed with stroke. The research question is as follows: What are the most commonly used therapeutic approaches in modulating spasticity in patients diagnosed with stroke, based on the results of clinical trials? The methodology is a literature review. Results: According to the studies analysed, the two most effective methods were electrotherapy and motor re-education. The effectiveness of each therapeutic approach may vary depending on the stage of stroke and the specific symptoms of spasticity. The selection of the most effective method for managing spasticity reduction in patients with CVE should be individualised and multidisciplinary, taking into account the specific symptoms of spasticity, the stage of CVE, and the patient's functional capacity.